If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k = 3(k + -1) + 7 Reorder the terms: 2k = 3(-1 + k) + 7 2k = (-1 * 3 + k * 3) + 7 2k = (-3 + 3k) + 7 Reorder the terms: 2k = -3 + 7 + 3k Combine like terms: -3 + 7 = 4 2k = 4 + 3k Solving 2k = 4 + 3k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-3k' to each side of the equation. 2k + -3k = 4 + 3k + -3k Combine like terms: 2k + -3k = -1k -1k = 4 + 3k + -3k Combine like terms: 3k + -3k = 0 -1k = 4 + 0 -1k = 4 Divide each side by '-1'. k = -4 Simplifying k = -4
| 3x^2-0=29 | | 21x^2+45x+54=0 | | 3x^2-29= | | 2x^2+3=101 | | -(2x-1)(3x+4)=0 | | 2(2x)(3a)= | | 2(j-5)=5(4j+1) | | 3x^2-28x-9=0 | | 160-7x=20x+16 | | 7-7x=99-35x | | d^2-10d+25=6 | | 30Y+20X=5 | | x^2+82x-2320=0 | | -3(3n+3)=12 | | 5x+7=113 | | 72=2x+(2w-10) | | 72=2x+(2w-5) | | 63=7x+2x+9 | | 72=2x+2w-5 | | 72=2x | | 4s-7=9 | | 12s-3=3 | | 13s-2=2 | | 9a-5=9 | | -26.3+0.1p=0.9p+5.3 | | 5.4y-7.5=2.22 | | 0.3z=-39 | | 1=t-0.002 | | 6x+39+11x+90=180 | | -31.8+n=-36 | | 6x+39+11x=180 | | 6y-6=36 |